2002
DOI: 10.1097/00008506-200207000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Type and Rate of Subarachnoid Fluid Infusion on Lethal Neurogenic Pulmonary Edema in Rats

Abstract: In patients who experience sudden death from spontaneous subarachnoid hemorrhage, more than 90% present with acute pulmonary edema. The underlying pathogenesis of this complication is poorly understood. In addition, the specific role of the extravasated blood products and the associated elevation in intracranial pressure leading to the systemic and pulmonary effects during subarachnoid hemorrhage are not well established. The authors tested a new model of acute and severe subarachnoid hemorrhage comparing fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The alveolar-arterial protein concentration ratio used in this model has some limitations. This ratio is an estimate of pulmonary permeability [19,20]; however, protein measurement in BAL may also include proteins from the local inflammatory reaction and surfactant proteins. Thus, the reported alveolar-arterial protein concentration ratio may be an overestimation of the pulmonary permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alveolar-arterial protein concentration ratio used in this model has some limitations. This ratio is an estimate of pulmonary permeability [19,20]; however, protein measurement in BAL may also include proteins from the local inflammatory reaction and surfactant proteins. Thus, the reported alveolar-arterial protein concentration ratio may be an overestimation of the pulmonary permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein concentration (plasma and BAL fluid proteins) at the end of the experiment (or just before death, if applicable) was measured in the supernatant by spectrophotometry (Bio-Rad Protein Assay; Bio-Rad Laboratories, Hercules, CA). The alveolar-arterial protein concentration ratio between alveolar and arterial plasma protein concentration per group was calculated to estimate pulmonary permeability [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary edema usually develops within after SAH, mechanisms that the CR activates, and the complications that follow; and ( c ) outlines the main mechanism by which transient global ischemia contributes to early brain injury after SAH hours after SAH; however, a delayed form that appears 3-5 days after SAH is also reported [ 35 ]. In animals, leakage of lung capillaries occurs 8 min after injection of blood into the cisterna magna [ 36 ]. The nature of mechanisms underlying SAH-related pulmonary edema are cardiogenic (myocardial dysfunction leading to a raised hydrostatic pressure and fl uid retention), noncardiogenic (such as acute lung injury or acute respiratory distress syndrome), and neurogenic (pressure of blood on respiratory centers at SAH) [ 34 , 35 ].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…[19] Moreover, it was reported that the amount, but not the type of fluid injected intrathecally had a significant impact on hemodynamic and respiratory parameters. [22]…”
Section: Discussionmentioning
confidence: 99%